Historical Population Database of Transylvania. A Database Manual - BOLOVAN, Ioan; CRĂCIUN, Bogdan; COVACI, Diana; DUMĂNESCU, Luminița; HOLOM, Elena-Crinela; MÂRZA, Daniela; LUMEZEANU, Angela-Cristina (Studia Universitatis Babeș-Bolyai Digitalia, 2020)
The Historical Population Database of Transylvania (HPDT) is a research tool developed by the Centre for Population Studies at Babeș-Bolyai University Cluj-Napoca starting with 2014, whose goal is to host digitalized information from parish registers – the main sources for population history in Transylvania and Hungary until 1895. The database is covering roughly the period 1850–1914: from the first modern census in the Austrian Empire to the upper limit allowed by the Romanian Law 16/1996 (i.e. a tresshold of 100 years, in the present day the limit being the year 1919). Curerntly, there are more than 400.000 individuals recorded within the database, which requires constant cleaning, standardization and linkage. The main objective of this undergoing entreprise consists in providing a research tool equally useful to the scientific milieu through its rich and complex data, and to the general public by means of its genealogical interface. The present work has the purpose to document the transcription and data entry processes related to HPDT, by detailing the rules applied in transferring the information from the primary sources into the digital framework.